Extension of the Simulation Model of Bubble Growth during Phase Change Heat Transfer Using Volume of the Fluid Flow Model. (6th July 2022) - Kalim, Muhammad; Ali, Asif Iqbal; Khan, Adnan
Abstract : Nucleate boiling is used in numerous engineering applications, such as the chemical, manufacturing, thermal, nuclear, and electronic industries. This research paper deals with the numerical analysis of bubble growth using a fluid flow model. This physical phenomenon of bubble growth has not been discussed mechanically and does not throw light on empirical models. We are discussing this phenomenon in another way to get the required results in this paper. Simulation of bubble growth is already published by measuring the volume of fluid flow; the method is known as VOFF tracking method. Lee's model has already discussed the phase change that occurs due to evaporation and condensation of the fluid. We have used the method in which the equation terms involving energy and mass source caused by phase change are incorporated into the control equations by additional subroutines written in C language. We have mentioned in detail the results of simulating mass transfer caused by phase change and the effect of subcooling on bubble growth. The results thus obtained show that the subcooling effect prevents the growth of bubbles from growing due to the certain amount of bubble caps in the subcooled area. The effect of evaporation of the liquid increases the size of the bubbles in both the subcooled and the superheated zone.